Indonesia's Capital Structure And Company Profitability Before And After The Implementation Of PSAK 73 - Amrie Firmansyah; Elisabeth Elisabeth; Estralita Trisnawati (JAS (Jurnal Akuntansi Syariah), 2023)
Statement of Financial Accounting Standards (PSAK) 73 regarding leases has been in effect since 2020 in Indonesia. The standard adopts International Financial Reporting Standards (IFRS) 16, which requires companies to record all lease transactions as finance leases. This study examines differences in capital structure and company profitability before and after implementing PSAK 73 in Indonesia. This study uses financial report data for retail and transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 and 2020 with a population of 160 observations. The secondary data is sourced from the Indonesia Stock Exchange website. Based on purposive sampling, the total number of observations that can be used in this study is 104 observations. Hypothesis testing was carried out using a paired sample t-test. This study found that in the first year after the implementation of PSAK 73, the capital structure from debt is higher than that from equity. This condition is different from the period before the implementation of PSAK 73. Then the level of profitability in the first year of implementation of PSAK 73 decreased compared to the period before the implementation of PSAK 73. This research recommends that the Financial Services Authority implement risk mitigation rules for companies registered on the IDX regarding the financial impact of Indonesia's new financial accounting standards.